Os contos de fadas e a construção de papéis sociais: uma experiência na Escola Municipal Avó Virgilina. - Lima, Obarda Aparecida Alves (Universidade Federal do Tocantins, 2020)
This research has as main objective to analyze the importance of fairy tales for the construction of social roles in the learning process in Early Childhood Education. In order to develop the study, a bibliographical research was carried out in such authors as Bastos (2015), Cruz (2009) Furini (2009) Martins (2010), Resurreição (2005), Ribeiro (2015), (Rligliski, 2012) . In addition, a field research was carried out at the Virgilina Grandmother Preschool with the purpose of verifying in the context of a preschool the reflection of the work with stories in the learning process in Early Childhood Education. After studying and analyzing the data, we verified the importance of fairy tales both in the learning of the students, and in the formation and development of the children becoming something that can help throughout life, moreover, it is a process that can have support and incentive parents in partnership with the school. The results of this research, both in the classroom activity and in the interview, and in the answers of the teacher's questionnaire, we can affirm that the reading of the fairy tales, has a great contribution to the learning of the students yes, as well as in the construction of social roles, this is evident in the observation in the room, and in the analysis of the answers, and in the whole research process that was carried out. Even if the school does not have complete improvement, and the necessary materials, what little it has, the teacher uses with its students, and it is through this that we can affirm that fairy tales besides being an important teaching tool, is a simple and enjoyable way to learn.